Use of data platforms and Google Earth Engine in criosphere education and climate change - Petsch, Carina; Velho, Luiz Felipe; Rosa, Kátia Kellem da (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
The proposal of this research is to present lesson plans, using ICT, to assist teachers in teaching climate change and Cryosphere in the Geography course. The lesson plans were constructed with objective items, class description, activity and target audience. Two classes (1 and 2) were proposed where concepts of the Cryosphere will be discussed and how their dynamics will be altered by the anthropic factor. Students will be encouraged to reflect on the effects of climate change on their city, and how strategies can be adopted to minimize these impacts (Lessons 4 and 5). Addressing the social context, a class (a 3) proposes to discuss how low-income communities will be affected. The lesson plans were organized according to a teaching-learning logic that encourages students to have a systemic view of the effects and impacts of climate change.